2004
DOI: 10.3310/hta8280
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and cost-effectiveness of imatinib for first-line treatment of chronic myeloid leukaemia in chronic phase: a systematic review and economic analysis

Abstract: Non-UK purchasers will have to pay a small fee for post and packing. For European countries the cost is £2 per monograph and for the rest of the world £3 per monograph.You can order HTA monographs from our Despatch Agents:-fax (with credit card or official purchase order) -post (with credit card or official purchase order or cheque) -phone during office hours (credit card only).Additionally the HTA website allows you either to pay securely by credit card or to print out your order and then post or fax it. NHS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(37 citation statements)
references
References 31 publications
0
34
0
3
Order By: Relevance
“…The utilities for AP and blast phase reported by Reed et al 116 are slightly different from those quoted by Dalziel et al, 65 although both are taken from the IRIS trial originally. 26,116,130 In the Reed et al analysis, 116 no difference was assumed between AP and blast phase, as the observed difference in values was not statistically significant.…”
Section: Utilities In Peninsula Technology Assessment Group Modelmentioning
confidence: 68%
See 1 more Smart Citation
“…The utilities for AP and blast phase reported by Reed et al 116 are slightly different from those quoted by Dalziel et al, 65 although both are taken from the IRIS trial originally. 26,116,130 In the Reed et al analysis, 116 no difference was assumed between AP and blast phase, as the observed difference in values was not statistically significant.…”
Section: Utilities In Peninsula Technology Assessment Group Modelmentioning
confidence: 68%
“…These data were collected for patients taking imatinib during the IRIS trial, 26 as reported by Reed et al 116 and used by Dalziel et al 65 in a previous HTA of imatinib for CML. These data are drawn from a large sample of patients, using the EQ-5D, which is preferred in the NICE reference case.…”
Section: Utilities In Peninsula Technology Assessment Group Modelmentioning
confidence: 99%
“…Cost comparisons with imatinib have shown favorable results in the US. 23,24 These findings appear not to apply in all countries.…”
mentioning
confidence: 81%
“…It is highly likely that such considerations will have an even stronger impact in the future for countries in the middle income category when modern expensive therapies such as iron chelation in thalassemia or antibody treatment in paroxysmal nocturnal hemoglobinuria will have to be compared with HSCT. [21][22][23][24][25][26][27] Our analysis has some limitations. Firstly, there is no uniform database on the incidence or prevalence of the individual disease categories in European countries.…”
mentioning
confidence: 99%